2023
DOI: 10.1007/s10995-023-03626-3
|View full text |Cite
|
Sign up to set email alerts
|

Parental Worry About COVID-19 in Preschool Children’s Mothers During the Pandemic Waves: The Role of Maternal Negative Feelings and Parenting Styles

Abstract: This cross-sectional study explores the relationship between maternal feelings, maternal parenting styles, and mothers’ worry about COVID-19’s detrimental consequences on preschool children’s health and well-being. The study is among the first to concentrate on this reference specific group, whose characteristics might be particularly vulnerable to COVID-19’s adversities. One hundred and four mothers of at least one preschool-age child completed an online questionnaire battery, which included the Parental Feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In this normative and highly resourced sample, the relationship between EA and EPII neg indicates that mothers and their children mutually affected one another’s behavior in nuanced ways. Interestingly, prior self-report studies have suggested that maternal hostility (not measured using EA) increased during the pandemic [ 62 , 63 ]. Our finding that increases in EPII neg lead to decreases in sensitivity and nonhostility not only align with these findings but provide a direct comparison between observational data and individual reported experiences of COVID-19-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this normative and highly resourced sample, the relationship between EA and EPII neg indicates that mothers and their children mutually affected one another’s behavior in nuanced ways. Interestingly, prior self-report studies have suggested that maternal hostility (not measured using EA) increased during the pandemic [ 62 , 63 ]. Our finding that increases in EPII neg lead to decreases in sensitivity and nonhostility not only align with these findings but provide a direct comparison between observational data and individual reported experiences of COVID-19-related stress.…”
Section: Discussionmentioning
confidence: 99%